Self‐regulation and frontal EEG alpha activity during infancy and early childhood: A multilevel meta‐analysis. Issue 6 (11th July 2022) - Hofstee, Marissa; Huijding, Jorg; Cuevas, Kimberly; Deković, Maja
Abstract: Integrating behavioral and neurophysiological measures has created new and advanced ways to understand the development of self‐regulation. Electroencephalography (EEG) has been used to examine how self‐regulatory processes are related to frontal alpha power during infancy and early childhood. However, findings across previous studies have been inconsistent. To address this issue, the current meta‐analysis synthesized all prior literature examining associations between individual differences in self‐regulation and frontal EEG alpha power (baseline and/or task). In total, 23 studies consisting of 1275 participants between 1 month and 6 years of age were included, which yielded 149 effect sizes. Findings of the three‐level meta‐analytic model demonstrated a non‐significant overall association between self‐regulation and frontal alpha power. Yet, significant moderating effects were found for self‐regulation construct (emotion regulation, effortful control, executive function), self‐regulation measurement (behavioral task, computer assessment, lab observation, questionnaire), and children's mean age. Self‐regulation was only significantly correlated with frontal alpha power when studies focused on the executive functioning construct. Moreover, the use of behavioral tasks or questionnaires and a higher mean age of the children resulted in small but significant effect size estimates. Higher frontal alpha power values were related to higher order top‐down mechanisms of self‐regulation, indicating that these mechanisms might become stronger when the frontal cortex is sufficiently developed. The findings of the current meta‐analysis highlight the importance of longitudinal analyses and multimethod approaches in future work to reach a more comprehensive understanding of the role of frontal EEG alpha activity in the etiology of individual differences in early self‐regulation. Research Highlights: The first meta‐analysis of individual differences in self‐regulation and frontal EEG alpha power during infancy and early childhood demonstrated a non‐significant overall association. Moderation analyses revealed that variations in frontal alpha power were significantly associated with executive function, but not with effortful control and emotion regulation. Frontal alpha power was related to variations in self‐regulation when measured by behavioral tasks and questionnaires, but not via computer assessments and lab observations. The association between individual differences in self‐regulation and frontal alpha power becomes significantly stronger with age. Abstract : The current study provides the first meta‐analytic synthesis of the literature on the relations between individual differences in self‐regulation and frontal EEG alpha power during infancy and early childhood. The association between self‐regulation and frontal alpha power only became significant when children were 3 years and older, when behavioral tasks or questionnaires were used as measures of self‐regulation, or when studies focused on the construct executive functioning. These findings indicate that top‐down mechanisms of self‐regulation, such as executive functioning, might become stronger when the frontal cortex is sufficiently developed to exert top‐down control for successful self‐regulatory skills.